Retificador monofásico três níveis com elevado fator de potência modificado para aplicações em UPS com ponto neutro comum entre a carga e as fontes CA/CC - Fernandes, Leonardo Göbel (2019)
The dependence of electronic equipment is something regular, and within this context there are systems whose operation is considered critical, that is, they cannot fail due to the power supply's lack of energy. The use of systems with uninterrupted power supply is shown as a solution to avoid monetary losses, or damages to human health, derived from these problems. Considering this scenario, it is proposed the development and implementation of a boost rectifier/converter, single phase, bridgeless, three levels with unit power factor. In addition, the search for equipment with a high electromagnetic compatibility made the development of this project as a requirement to implement a converter with a common neutral point between the bank of batteries, mains and the load. The theoretical analysis of the conduction stages, as well as the equations that define the behavior of the proposed converter are presented together with simulations. The practical results aimed to meeting the main parameters of the project: effective input voltage of 127 V, battery bank voltage of 180 V, output power of up to 2,5 kW; which yielded an efficiency above 95% for rated power. The use of a digital signal controller, model MC56F84763 from Freescale Semiconductor®, was used on the implementation of the power factor correction strategy, as well as to allow load transients and source switching with stabilization in a short period of time (<16,66 ms). From the results obtained it is possible to affirm that the development of this project serves as a precedent for researches that aim to associate an AC/DC-DC rectifier/converter for UPS systems with high electromagnetic compatibility, unit power factor and high efficiency, characteristics that guarantee a high quality and uninterrupted energy.